Fair play : the ethics of sport - Simon, Robert L., 1941- (Boulder, CO : Westview Press, 2015)
"Addressing both collegiate and professional sports, the updated edition of Fair Play: The Ethics of Sport explores the ethical presuppositions of competitive athletics and their connection both to ethical theory and to concrete moral dilemmas that arise in actual athletic competition. The addition of two new authors for this edition, Cesar R. Torres and Peter F. Hager, bring to the book a discussion of the moral issues involved in youth sports and the ethics of being a fan as well as a fresh perspective on developing the theories of broad internalism and the quest for excellence. Furthermore, major criticisms of broad internalism by philosophers William J. Morgan and Scott Kretchmar add a new dimension to the discussion on the moral foundations of winning"--
Introduction : The Ethics of Sports -- Theories of Sport : Frameworks for Evaluation -- Ethics in Competition : Cheating, Good Sports and Tainted Victories -- Drugs, Genes, and Enhancing Performance in Sport -- Gender Equity in Sport : What Does Justice Require? -- Sports on Campus : Intercollegiate Sports and Their Critics -- The Commercialization of Sport : Marketing and Corruption in Competitive Athletics -- Sport, Moral Education, and Social Responsibility.
Includes bibliographical references and index.
Keywords: Sports -- Moral and ethical aspects; Sports -- Social aspects